DC energy meter / Rohasdiana Rozali - Rozali, Rohasdiana (2013)
This development of Direct Current (DC) energy meter as measurement device that measure amount of energy supplied by DC source. The objective of this study is to design and develop DC energy meter that operate by using microcontroller PIC 16F873A. This development also involved study on the DC energy meter circuit and layout and understand the components functions. Development of this DC energy meter involved software programming and hardware design method.